One year Survival Rate of Ketac Molar versus Vitro Molar for Occlusoproximal ART Restorations: a RCT. - Olegário da Costa, Isabel (My University, 2017)
Good survival rates for single-surface Atraumatic Restorative Treatment (ART) restorations have been reported, while multi-surface ART restorations have not shown similar results. The aim of this study was to evaluate the survival rate of occluso-proximal ART restorations using two different filling materials: Ketac Molar EasyMix (3M ESPE) and Vitro Molar (DFL). A total of 117 primary molars with occluso-proximal caries lesions were selected in 4 to 8 years old children in Barueri city, Brazil. Only one tooth was selected per child. The subjetcs were randomly allocated in two groups according to the filling material. All treatments were performed following the ART premises and all restorations were evaluated after 2, 6 and 12 months. Restoration survival was evaluated using Kaplan-Meier survival analysis and Log-rank test, while Cox regression analysis was used for testing association with clinical factors (α = 5%). There was no difference in survival rate between the materials tested, (HR = 1.60, CI = 0.98–2.62, p = 0.058). The overall survival rate of restorations was 42.74% and the survival rate per group was Ketac Molar = 50,8% and Vitro Molar G2 = 34.5%). Cox regression test showed no association between the analyzed clinical variables and the success of the restorations. After 12 months evaluation, no difference in the survival rate of ART occluso-proximal restorations was found between tested materials.
PUBLISHED
Keywords: Glass Ionomer Cements; Pediatric Dentistry; Tooth; Deciduous